2014
DOI: 10.1016/j.jvs.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, randomized study of cutting balloon angioplasty versus conventional balloon angioplasty for the treatment of hemodialysis access stenoses

Abstract: Cutting balloon angioplasty proved to be a safe and effective treatment of graft-to-vein anastomotic stenosis, with significantly higher patency than that of conventional balloon angioplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 19 publications
2
46
0
1
Order By: Relevance
“…In addition, the inflammatory response triggered by interventions may be another predictor of restenosis. Consequently, modification of devices or techniques to limit vessel injury, such as cutting balloons or graft stents, may be beneficial in mitigating restenosis after PTA of AVFs (26,27,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the inflammatory response triggered by interventions may be another predictor of restenosis. Consequently, modification of devices or techniques to limit vessel injury, such as cutting balloons or graft stents, may be beneficial in mitigating restenosis after PTA of AVFs (26,27,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…concluded that treatment of hemodialysis access stenoses with percutaneous cutting balloon angioplasty resulted in higher long‐term patency at 6 months compared to conventional balloon angioplasty . However, considerable heterogeneity between the patient populations of the three included studies warrants re‐considering this conclusion …”
mentioning
confidence: 99%
“…compared cutting and high‐pressure balloon angioplasty exclusively in patients with AV grafts, not AV fistulas. The title of Agarwal et al 's study uses ‘arteriovenous fistula’ which could be considered misleading when patients with AV grafts are included in two of the studies …”
mentioning
confidence: 99%
See 2 more Smart Citations